DESIGN AND ASSEMBLY OF A LOW FREQUENCY CONDUCTIVITY ELECTRODES AMORPHOUS CARBON - Cjuno H., Jesús A. (2005)
lt has been designed and built a conductimeter that operates with alternating current of 700 mÅ, 7.85 V and frequency among 50 - 60 Hz. For the voltage measures and amperage, a digital multimeter CIE- 123 with 2000 mΩ. Two electrodes were used, one built with two bars of amorphous coal and another of platinum normalized. For comparative ends, a normalized conductimeter Hanna HI98129 has been used. The values of conductivity obtained according to the official protocols, they are compatible with the references them and the comparison apparatus.